Anti-gender discourse in the Serbian media - Bobičić, Nađa; Stojčić, Marijana (CM: Communication and Media ISSN 2466-541X; 2466-5452 (Online), 2023)
Main goal of the text is a feminist critical analysis of anti-gender discourses in 892 media texts published in Serbia, in the period from January 1, 2019 to October 31, 2022. The media base that includes the largest part of the mainstream media on the territory of Serbia was selected. The analysis was done on a targeted sample by searching for several key terms, characteristic of anti-gender discourses: "gender ideology", "family values" and "traditional values".The research showed that the discourse of the anti-gender movement in Serbia corresponds to the discursive framework and wider action of the international anti-gender movement, confronting feminism, the action of LGBTIQ+ movement and, in general, progressive movements. As in the case of the international anti-gender movement, relying on an essentialist and biological understanding of gender and sexuality and insisting on a traditionalist family structure, based on gender asymmetry and social hierarchies, is part of a broader rejection of ideas and practices of social and human equality. Only in this context it becomes more clear why ideas about the social conditioning of gender and the fluidity of human identities, as well as the equality of different manifestations of sexuality are considered so subversive.
Keywords: feminist critical discourse analysis, anti-gender discourse, gender ideology, family values, media, Serbia